Collaborative innovation and absorptive capacity as an antecedent on IT firm financial performance - Mata, M. N.; Martins, J. M.; Inácio, P. L. (Journal of the Knowledge Economy, 2024)
A lack of collaborative innovation and absorptive capacity in firms causes projects to fail. Managers/employees in small and medium enterprises (SMEs) are not sufficiently aware of the practices of intellectual capital and nor do they collect, share, transfer, and utilize knowledge properly. This current study, therefore, focuses on the relationship between collaborative innovation and the financial performance of Portuguese IT sector SMEs, with a mediating role of absorptive capacity and a moderating role of intellectual capital based on three sub-domains (human capital, organizational capital, and social capital). Close-ended questionnaires were used to obtain data from 308 employees and managers. Owing to the COVID-19 pandemic, data were also collected through an online survey method. The simple random sampling technique was used to collect data and analyze it using the PLS-SEM method. The results show that collaborative innovation has a positive and significant impact on the financial performance of IT firms in Portugal. Absorptive capacity is considered a potential mediator between collaborative innovation and financial performance. Moreover, the moderating role of intellectual capital strengthens the relationship between collaborative innovation and absorptive capacity.